Tourism Assets Management Strategy In Rote Ndao District – Nusa Tenggara Timur - Cicilia Apriliana Tungga; Olivia L.E. Tomasowa (Eduvest - Journal of Universal Studies, 2021)
Ndao Regency is one of the regencies that prioritizes the direction of development for 2019-2024 in the tourism sector. The problem in Rote Ndao District is the absence of asset management that focuses on potential tourism assets. In this study, the formulation of the problem is to place a tourism asset management strategy in Rote Ndao Regency. The purpose of this study is to evaluate, identify and describe the management of regional assets. This study also formulates priority strategies to improve local asset management of the Rote Ndao District Government. The data consisted of primary and secondary data. Primary data were obtained from direct observation, interviews and questionnaires using purposive sampling method. While secondary data obtained from literature and documents relevant to the research. The analysis in this study uses a SWOT analysis. The results of the study indicate that the weak competence of human resources in asset management is due to the lack of guidance, supervision, lack of supporting facilities and infrastructure and the lack of cooperation involving the private sector and the community to develop tourism potential. The control system affects the performance of regional asset management. The prioritized strategy is to improve the quality of human resources in managing and reporting local government assets.